Human Rights in Transition: a Research if Legal, Ethical, and Policy Dimensions - Permata sakti (Legal Frontier, 2025)
This research explores the intersection of legal, ethical, and policy dimensions in transitional human rights, aiming to identify trends, challenges, and frameworks in the context of post-conflict and political transitions. The study adheres to established guidelines (PRISMA) and systematically analyzes peer-reviewed studies, case studies, and reports from reputable databases, with a focus on diverse regions and transitional contexts. Key findings highlight the complexities in balancing legal accountability with the ethical imperative of national reconciliation, and the pivotal role of international organizations in shaping transitional justice policies. The review underscores significant gaps, including the underexplored intersectionality of human rights violations, emerging issues like digital rights, and the impact of climate change on human rights transitions. By synthesizing existing literature, the review provides critical insights into the evolving nature of transitional justice, emphasizing the need for adaptive, interdisciplinary approaches that consider local contexts and emerging global challenges. The implications of the findings call for a shift toward context-sensitive, integrated frameworks for human rights advocacy and governance, offering a foundation for future research and policy innovation in transitional human rights